2017
DOI: 10.1089/sur.2017.129
|View full text |Cite
|
Sign up to set email alerts
|

Surgery versus Antibiotics for Uncomplicated Appendicitis: Which Would a Medical Student Want?

Abstract: When informed of the benefits and risks of surgery and antibiotics to treat AUA, medical students in our study were more likely to choose surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…25 Another study showed that after information about the risks and advantages of surgery and antibiotic treatment for uncomplicated acute appendicitis, a population of medical students were more inclined to choose surgery, also noting that the answers may have been influenced by the manner in which the summary data of each treatment arm were presented. 26 A recent guideline 27 states that nonoperative management of uncomplicated acute appendicitis is feasible in patients wishing to avoid surgery and accept the risk of recurrence. With an increasing amount of studies, [4][5][6][7][8] meta-analyses, 9-11 and long-term follow-up results 12 indicating the feasibility of antibiotic therapy in the treatment of uncomplicated acute appendicitis, future studies should focus on a more multifactorial approach to making the treatment decision, including patient information and involvement in shared decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…25 Another study showed that after information about the risks and advantages of surgery and antibiotic treatment for uncomplicated acute appendicitis, a population of medical students were more inclined to choose surgery, also noting that the answers may have been influenced by the manner in which the summary data of each treatment arm were presented. 26 A recent guideline 27 states that nonoperative management of uncomplicated acute appendicitis is feasible in patients wishing to avoid surgery and accept the risk of recurrence. With an increasing amount of studies, [4][5][6][7][8] meta-analyses, 9-11 and long-term follow-up results 12 indicating the feasibility of antibiotic therapy in the treatment of uncomplicated acute appendicitis, future studies should focus on a more multifactorial approach to making the treatment decision, including patient information and involvement in shared decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of previous similar studies have investigated knowledge about appendicitis and its treatment, as well as attitudes towards non-operative treatment of appendicitis, with mixed observations [ 14 , 15 , 16 , 17 , 18 ]. To the best of our knowledge, no previous investigation has been undertaken in the UK, with the majority conducted in the USA.…”
Section: Discussionmentioning
confidence: 99%
“…They reasoned that medical students were in a unique position of being potential patients with greater medical knowledge than the general public and, possibly, less bias than practicing physicians. Two-thirds of respondents expressed a preference for surgical treatment, while 24% expressed a preference for non-operative treatment [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In selecting the right treatment option, it is important to acknowledge the patient’s preferences for non-operative or operative treatment. Few studies have described the patient’s choice for treatment of uncomplicated appendicitis, and a wide range of patients preferring non-operative treatment has been reported, varying from 9.4% to 57% 22–24. This wide range may be explained by the different ways of informing the participants and by the type of the included patients.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have described the patient’s choice for treatment of uncomplicated appendicitis, and a wide range of patients preferring non-operative treatment has been reported, varying from 9.4% to 57%. 22–24 This wide range may be explained by the different ways of informing the participants and by the type of the included patients. To facilitate shared decision making for uncomplicated appendicitis, the correct group of participants should be surveyed, and accurate information must be provided about the risks and advantages of both antibiotic and surgical treatment.…”
Section: Introductionmentioning
confidence: 99%